From coercion to deception: the changing nature of police interrogation in America - Leo, Richard A. (Crime, law and social change, 1992)
Our police, with no legal sanction whatever, employ duress, threat, bullying, a vast amount of moderate physical abuse and a certain degree of outright torture; and their inquisitions customarily begin with the demand: "If you know what's good for you, you'll confess. (Ernest Jerome Hopkins, 1931)1. Today, Ness Said, interrogation is not a matter of forcing suspects to confess but of "conning" them. "Really, what we do is just to bullshit them" (William Hart, 1981)2. There is an interesting irony at work here: restrict police use of coercion, and the use of deception increases. (Gary Marx, 1988)3. In both popular discourse and academic scholarship one continually encounters references to the "tradition-bound" police who are resistant to change. Nothing could be further from the truth. The history of the American police over the past 100 years is the history of drastic, if not radical, change. (Samuel Walker, 1977)4.